Effect of Inclusion Body Hepatitis disease in Iraq Broiler Chikens (Texas Journal of Agriculture and Biological Sciences, 2022)
The viral disease known as inclusion body hepatitis (IBH) spreads rapidly among chicken flocks.Thisdisease had been described in Iraq, since 1970s. However, in the recent few years, the severity and mortalityof the disease have been dramatically increased in our region. In this article, we sought to describe anddetect the causative agent serotype depending on molecular bases. For further confirmation, histologicalmethods have also been used for better understanding.For this purpose, young broiler (18 – 22 day old) withacute IBH infection collected from four distinct geographical regions have been subject to the study. Liverswere taken under sterile conditions for histopathological study. Hematoxylin and eosin (H & S) stains wereused to examine liver tissue that had been sectioned at 5 microns and embedded in paraffin blocks formicroscopic examination.Our findings suggest that the serotype of the IBH in Iraq is fowl adenoviruses (FAdVs). The samplesshowed severe reactions where acute hepatitis is prominent with hepatic necrosis and massive basophilic andeosinophilic intranuclear inclusion bodies. Other, non-specific histopathological changes have also beenreported such as infiltration of inflammatory cells, hemorrhages and edema